Implementasi Kebijakan Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat di Polres Morowali Utara - Sonny Rivaldo Mandias; Nawawi Natsir; Abdul Hamid (CV. Rayyan Dwi Bharata, 2026)
This study aims to determine the implementation of the Bhayangkara Policy for Maintaining Public Security and Order at the North Morowali Police. This study uses qualitative data collection methods. The research location is at the North Morowali Police Station. The theory used in this study is the theory put forward by George C. Edward III. Seven informants participated in this study. Data were obtained from observations, interviews, and documentation. The data analysis methods included data collection, data condensation, data presentation, and conclusion drawing/verification. The research concludes that the policy's implementation has not been optimal. This is evident in four key aspects of public policy implementation: communication, resources, disposition, and bureaucratic structure, which still face various obstacles. First, from a communication perspective, coordination between leaders, implementers, and the assisted community has not been effective. Instructions and information regarding the implementation of Bhabinkamtibmas duties are often not conveyed clearly and consistently. The lack of outreach to the community also results in low public understanding of the Bhabinkamtibmas' role and function. Second, from a resource perspective, the limited number of Bhabinkamtibmas personnel and supporting facilities such as operational vehicles, communication equipment, and budget support have resulted in suboptimal implementation of duties in the field. Third, from an implementation perspective, the commitment and motivation of some Bhabinkamtibmas members in carrying out community development duties are still low. Fourth, from a bureaucratic perspective, the work mechanisms and coordination between divisions within the Police Resort and between the Police Resort and the local government are not yet fully integrated.